Interpretasi Teori Ocean Personality Traits pada Film The Secret: Dare to Dream (2020) - Herari, Noprita; Rubiyanto, Rubiyanto; Muhammad Fikri Akbar (CARAKA : Indonesia Journal of Communication, 2025)
The COVID-19 pandemic does not provide many options for finding entertainment media through activities at home. One of the most popular entertainment media is watching movies, or commonly known as cinematherapy. A film as an audio-visual medium that can provide a new picture of reality to think positively when going through difficult times in life, has attracted the attention of researchers. The film The Secret: Dare to Dream (2020) is considered the right object in this study. The formulation of the problem and the purpose of this research is, how to interpret the psychological theory of OCEAN Personality Traits described in the film The Secret: Dare to Dream (2020). Using the semiotic model of Roland Barthes, which separates the meaning of denotation, connotation and myth, the researcher conducts an analysis behind a script or transcription of the words of the characters in the film. The results of the analysis in this study provide an answer that, the two main characters in the film The Secret: Dare to Dream (2020) have contradictory personalities. The Secret: Dare to Dream movie nicely depicts the significant difference between optimistic characters against pessimistic characters in going through difficult times in life. The film The Secret: Dare to Dream is considered appropriate as an entertainment medium that is enjoyed at low times in life, especially during the COVID-19 pandemic that has hit since 2020.